Curare as an adjuvant to general anesthesia in the dog - Pickett, Deets, 1885-, author; Farquharson, James, advisor; Jensen, Rue, committee member; Deem, Arthur W., committee member; Binkley, A. M. (Almond Madison), 1900-, committee member (Colorado State University. Libraries, 1948)
To view the abstract, please see the full text of the document.
Keywords: Curare; Dogs